Sistem Monitoring Kudus Cegah Stunting (Sikating) Berbasis Website Di Kabupaten Kudus - Bagus Pramono, Wakhid; Setiaji , Pratomo; Muzid, Syafiul (Sekolah Tinggi Teknologi Dumai, 2025)
Stunting is a serious health problem that has a long-term impact on the quality of human resources, especially in remote areas such as Kudus Regency which have limited access to health services. This study aims to develop a web-based stunting prevention monitoring information system called SIKATING (Kudus Information System to Prevent Stunting) to replace manual recording methods that are prone to errors and delays. The method used in this study is software engineering with a descriptive approach and a waterfall system development model, while data is collected through observation and interviews with health workers in the field. The results of the study show that the SIKATING system is able to integrate toddler data recording, nutritional status analysis based on anthropometric indicators, notification to parents regarding toddler growth, and visual reporting in the form of graphs. The implementation of this system significantly increases the efficiency of the monitoring process, enables early detection of stunting cases, and supports data-based decision making by policy makers and health workers. Thus, this system has great potential to support the acceleration of sustainable stunting control in areas with limited access to health care.